Nuclear 0ν2β decays in B-L symmetric SUSY model and in TeV scale left–right symmetric model. (1st August 2022) - Yang, Jin-Lei; Chang, Chao-Hsi; Feng, Tai-Fu
Abstract: In this paper, we take the B-L supersymmetric standard model (B-LSSM) and TeV scale left–right symmetric model (LRSM) as two representations of the two kinds of new physics models to study the nuclear neutrinoless double beta decays (0 ν 2 β ) so as to see the senses onto these two kinds of models when the decays are taken into account additionally. Within the parameter spaces allowed by all the existing experimental data, the decay half-life of the nucleus 76 Ge and 136 Xe, T 1 / 2 0 ν ( 76 Ge, 136 Xe), is precisely calculated and the results are presented properly. Based on the numerical results, we conclude that there is greater room for LRSM type models than for B-LSSM type models in foreseeable future experimental observations on the decays.